Assessment of Stone Mastic Asphalt Performance in Road Pavements: A Comprehensive Review (Sebha University Conference Proceedings, 2025)
Pavement structures are fundamental to road infrastructure, where durability and performance directly influence service life and sustainability. Stone Mastic Asphalt (SMA) has emerged as a superior asphalt mixture due to its stone-on-stone aggregate skeleton, which enhances volumetric stability and resistance to permanent deformation. This study reviews the performance enhancement of SMA through the incorporation of sustainable fillers and recycled materials as alternatives to conventional fillers. Compared to traditional dense-graded asphalt, SMA demonstrates up to 30–40% greater rutting resistance under heavy traffic loading. The inclusion of fibres, typically at 0.3–0.5% by weight, increases mixture stability by 15–25% and reduces binder drain-down by approximately 50%, promoting uniformity during placement. The volumetric behaviour of SMA is governed by the balance between mastic content and air voids; increasing the mastic by 1–2% reduces voids and enhances durability. Polymer modification of the asphalt binder further improves cohesion and adhesion, resulting in superior moisture resistance (Tensile Strength Ratio, TSR > 80%). Moreover, the use of sustainable fillers contributes to improved rutting resistance and long-term structural performance. However, optimal outcomes depend on precise mix design, appropriate material selection, and high-quality construction practices.